Seedling Selection Using Molecular Approach for Ex Situ Conservation of Critically Endangered Tree Species (Vatica bantamensis (Hassk.) Benth. & Hook. ex Miq.) in Java, Indonesia. (May 2019) - Kusuma, Yayan Wahyu C.; Ariati, Siti R.; Risna, Rosniati A.; Mitsuyuki, Chika; Suyama, Yoshihisa; Isagi, Yuji
Ex situ conservation is an important complementary strategy for in situ to conserve endangered plant species. However, the limited areas designated for ex situ conservation such as in botanic gardens have become a great challenge for conservation practitioners and scientists attempting to optimally conserve the genetic diversity of targeted plant species. Our study aimed to assess genetic diversity and structure of wild seedlings of Vatica bantamensis, an endemic and critically endangered dipterocarp from Java (Indonesia). We also estimated genetic differentiation between the wild seedlings and existing ex situ collection and evaluated the genetic diversity preserved in the ex situ collection. Our analysis, using 730 single-nucleotide polymorphisms loci, showed that wild seedlings exhibited higher genetic diversity than the ex situ collection (nucleotide diversity, µ = 0.26 and 0.16, respectively). Significant genetic differentiation was also detected ( F ST = 0.32) between wild seedlings and ex situ collection. Furthermore, we found high kinship within the ex situ collection suggesting low genetic diversity since the founding collection. We also detected three distinct genetic clusters from all samples combined (analysis of molecular variance, ϕ = 0.48, p < .001), with two clusters present in the wild seedlings that were not represented in the ex situ collection. We recommend that supplementary collections from the two newly identified genetic clusters in the wild seedlings should be incorporated to increase genetic diversity in the ex situ collection. Furthermore, our study demonstrated that understanding the population genetics of targeted endangered species provides better results for ex situ conservation strategies.